What's wrong with fairness? How discourses in higher education literature support gender inequalities. Issue 1 (2nd January 2018) - Beddoes, Kacey; Schimpf, Corey
ABSTRACT: The role and influence of department heads on women in academia is understudied and weakly conceptualized. This article expounds on prior work, which identified limitations of department head literature, to put forth three problematic discourses that run through much of the department head research: the discourse of fairness, the discourse of collective good, and the training imperative . The discourse of fairness encourages an unproblematized adoption of fairness as a core criterion, ignoring the ways fairness may be conceptualized to benefit some groups over others. The discourse of collective good encourages department heads to seek out resolutions that maximize the 'good' for the department and its constituents but may perpetuate gender biases. The training imperative discourse places a heavy emphasis on training, regardless of whether training is or is not an effective means to address gender inequalities. Implications and directions for future work and practices are discussed in closing.